Talking hope – Dirkie Smit and public theology - Landman, Christina (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Dirkie Smit creating dialogical space between Habermas’ criticism of rationality and the criticism of experience required by the South African context of poverty and gender bias is explored. The contribution of Smit’s public voice is argued in terms of a criticism of survival which is as yet unsuccessfully lodged from the “private” spaces of the geographically marginalised, that is, believers living in rural “townships” who do not have access to public spheres or theology. It is concluded that Smit’s contextualisation of Habermas’ call for a critical rationality in the public sphere finds a legitimate place in him “talking hope”, albeit rationally limited, to people who are still oppressed by illiteracy and genderised behaviour. It is proposed that Smit expands the criticism of rationality which he holds in common with Habermas, to a prophetic and public voice that is based on a criticism of experience and survival in which the voices and needs of the voiceless will be heard and contra-cultured.